P13 Social, biological, behavioural and psychological factors and physical activity during pregnancy: a cross-sectional study. (2nd September 2017) - Flannery, C; Dahly, D; Byrne, M; Khashan, Ali; McHugh, S; Kenny, L; McAuliffe, FM; Kearney, PM
Abstract : Background: Regular Physical Activity (PA) during pregnancy is associated with a number of health benefits such as preventing pregnancy complications, limiting pregnancy weight gain, and decreasing the risk of gestational diabetes. Despite this, women's PA levels often reduce or cease during pregnancy. Various factors like body mass index, unemployment, and educational levels have been shown to be associated with PA levels during pregnancy. Using the Screening for Pregnancy Endpoint (SCOPE) data, this study aimed to examine the association of health behaviours and psychological well-being on PA levels in pregnancy using the biopsychosocial model. Methods: Nulliparous women with a singleton pregnancy were recruited from a large academic maternity hospital in Cork, Ireland (CUMH) as part of the international SCOPE study. Data was collected at 15±1 week's gestation including personal information, lifestyle and psychological measures. The outcome of interest was PA categorised as low, moderate or high levels and covariates were selected using the biopsychosocial model including social (age; years of schooling; socioeconomic status), biological (body mass index), behavioural (diet; smoking) and psychological factors (anxiety; response to pregnancy). Univariate and multivariable multinomial logistic regression examined the association between covariates and PA using Stata IC13. Results: 1774 pregnant women were recruited to SCOPE and women were classified as having low (22.3%), moderate (54.4%) or high (23.4%) PA levels (n=1766). In the fully adjusted model, preliminary findings indicate that age categories 30–34 years (OR 2.34 [95% CI: 1.26–4.37]), ≥35 years (OR 2.06 [95% CI: 1.01–4.19]) compared to those <25 years were positively associated with high PA levels. Having more than 12 years of schooling and a higher socioeconomic status remained significant (p<0.05) for moderate PA levels. Five portions of fruit and veg a day (OR 1.89 [95% CI: 1.21–2.94]), fish consumption (OR 1.47 [95% CI: 1.07–2.03]) and psychological response to pregnancy (OR 1.04 [95% CI: 1.01–1.08]) were also positively associated with high levels of PA. Women who reported smoking in their first trimester were 31% less likely to be in the high physical activity group compared to those who reported no smoking (OR 0.69 [95% CI: 0.49–0.99]). None of the biological factors were associated with high levels of PA. Conclusion: Social and behavioural factors appear to be the most influential factors driving PA levels. The results should be used to guide the development of educational campaigns and behaviour change intervention to encourage younger women to be active and to target those with lower education attainment and of lower socioeconomic status.